Molecular detection and characterization of pathogenic leptospira species in environmental samples of selected districts in Perak, Malaysia - Yap, May Ling (2019)
Leptospirosis is an endemic zoonotic disease in Malaysia caused by pathogenic species of genus Leptospira. Most cases of human leptospirosis are resulted from environmental exposure to water and soils contaminated with bacteria shed in urine of infected carrier animals. Epidemiological information about leptospirosis and Leptospira in the Perak state is scarce despite high disease incidence and mortality rate. To assess public health risk for leptospirosis, this study aims to determine the cross-sectional prevalence of pathogenic Leptospira in recreational and residential public places, as well as to characterize the genetic diversity of pathogenic Leptospira isolated from environmental samples. A total of 228 environmental water and shore soils samples were collected from 20 amenity forests and wet markets, filtered, and subjected to cultivation of leptospires in enriched EMJH medium. Presence of pathogenic Leptospira was confirmed by specific amplification of lipL32 gene by polymerase chain reaction (PCR). Results showed a high prevalence of pathogens (11 %, n = 25) throughout Perak, with highly varied localised prevalence among 13 positive sampling sites (6.7 - 41.7 %). Further distribution analysis implies a higher exposure risk in amenity forests than wet markets, through soil than water, as well as in the districts Kampar and Kinta than Batang Padang, Kuala Kangsar, Kerian, Larut, Matang & Selama. Unexpectedly the localised prevalence was not significantly associated with provision of waste management and site cleanliness. In addition to that, the total absence of pathogen at sites BF, GF, KW, LI, MM, PF, and SS in this present study has no relation to environmental parameters of samples, including temperature, pH, and water salinity. On another hand, seeking a sensitive molecular detection tool for accurate surveillance has driven this study to compare performance of other pathogen-specific diagnostic PCR assays on the positive samples. Unexpectedly a notably low and varied detection sensitivity (12 - 83 %) was determined among environmental isolates in relation to reference Leptospira strains sourced from human or animal hosts. ii Among genetic markers studied, lipL32 and flaB have been most prevalent, followed by gyrB and lfb1, whereas PCRs targeting secY and ligB showed high false-negativity. The absence of amplification was most likely attributed to mismatch in primer-annealing sites owing to high sequence polymorphisms. Phylogenetic analysis of partial 16S rRNA gene sequences revealed a subclade formed by all environmental isolates (except intermediate KF4) within the ‘pathogens’ clade, suggesting a fair distance from described host- associated Leptospira strains despite the low bootstrap values. A noticeable clustering of isolates sourced from similar sampling site, district, nor ecological niches was not observed. Through comparative polymorphic nucleotide analysis, ten pathogenic isolates were found closest to L. kmetyi and L. alstonii which have been prevailing in Malaysia, while the others probably represent novel species. In conclusion, genetically diverse pathogenic Leptospira spp. was widely distributed in Perak. Determining the virulence potential and whole- genome sequence for these atypical pathogenic isolates is important to validate the risk of leptospirosis, evolutionary relationship and reclassification of genus Leptospira.